Memorials of a consecrated life, - Lutton, Anne, 1791-1881 (AM Scholar: Women's Studies., 1882)
The memoir of Anne Lutton (1791-1881), written in a lively, formal style, describes her personal and family memories and experiences, from childhood to young adulthood. Lutton's narrative maintains a high moral tone throughout, and includes discussion on serious religious questions.